Comparative analysis of the quality of detection of air objects by secondary radar systems - Svyd, I.V. (Radiotekhnika, 2023)
The work is devoted to a comparative analysis of the quality of detection of air objects by secondary radar systems. The purpose of the work is a comparative analysis of the optimal and quasi-optimal structure for detecting air objects by secondary interrogation radar systems. A significant role in the information support of the airspace control and air traffic control system is played by secondary radar systems for airspace surveillance, which include secondary radars and identification problems on the basis of “friend or foe” identification. Note that in existing networks of radar surveillance systems, tracking of airborne objects is usually carried out using information from primary radar surveillance systems, and secondary radar surveillance systems are used as sources of additional radar information. In this regard, the problems of assessing the quality of detection of air objects by secondary radar systems, the specifics of the construction and operation of which differ significantly from the primary airspace surveillance radar systems, are relevant. Thus, increasing the probabilistic characteristics of the system of secondary radar systems when an aircraft transponder operates in the field of significant flows of intentional and intra-system interference is ensured by choosing detection thresholds depending on the values of the transponder readiness coefficient and the probability of suppression of individual response signal pulses. On the other hand, the use of detection thresholds on secondary radar systems that are optimal for the given operating conditions of the transponder makes it possible to reduce the requirements for the throughput of the aircraft transponder with a significant intensity of flows of intra-system and intentional correlated interference. Analysis of the characteristics of detection of air objects by secondary radar systems shows that: optimal thresholds for detecting air objects in secondary radar systems significantly depend on the readiness factor of the aircraft transponder and the probability of suppression of individual pulses of response signals in the response channel; the use of decoding response signals and subsequent accumulation when choosing the optimal threshold significantly reduces the detection quality indicators compared to optimal processing of a burst of response signals; the digital threshold for detecting air objects in a secondary radar system largely depends on the probability of signal suppression in the request channel and response channel.